Heat and Mass Transfer at Hot Surface Ignition of Coal Particle; MATEC Web of Conferences; Vol. 23 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment - Glushkov D. O. Dmitry Olegovich; Kosintsev A. G. Andrey; Shlegel N. E. Nikita Evgenjevich; Vershinina K. Yu. Kseniya Yurievna (2015, 2015)
Title screen